Analytical Review of Digital Accessibility Services on Official Sites of the World’s Best Universities - E. A. Kosova (Высшее образование в России)
The paper discusses the problem of e-learning accessibility for persons with disabilities. Development of e-learning content accessible to all students is gaining special relevance in the context of global trends in higher education related to the massive transition of learning to distance and hybrid formats. Based on the analysis of the official websites of 25 world’s top universities (according to the QS World University Rankings 2021), data on university digital accessibility services were systematized. The data search was carried out by total browsing of university sites’ structure and headings and by keywords. Data on 14 checklist categories were registered. Signs of administrative and project activities in the field of digital accessibility were found for 20 universities (80%), among which 10 (40%) have specialized structural subdivisions for digital accessibility. The content of digital accessibility web services contains data on the following topics: training in digital accessibility for educational content for authors and developers (14 university sites – 56%); a guide for authors (15–60%) and web developers (12–48%); consulting and assistance for authors and web developers (17–68%); accessibility examination (5–20%); legal norms (11–44%) and accessibility standards (16–64%); accessibility testing guide (16–64%); procurement requirements for accessible web products and services (8–32%); frequently asked questions (6–24%), etc. Based on the results of the analysis, the model of university digital accessibility services was developed and corresponding web site was published. It seems important to create similar web resources and corresponding structural subdivisions in universities of the Russian Federation, as well as to approve the intra-university local acts regulating the mandatory fulfillment of digital accessibility requirements in the development of educational content and the procurement of digital products and services. GOST R 52872-2019, based on WCAG 2.1, should be used as the basis for local legal regulations.